Sex differences in locomotor response associated with amphetamine administration - Benedetto, María Mercedes (2022)
Fil: Benedetto, María Mercedes. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigación Médica Mercedes y Martín Ferreyra; Argentina.